Adolescent quality of life and health behaviors: a comparative study between adolescents from the south of Portugal and Spain - Lima-Serrano,Marta (2013)
An observational, transversal study was carried out to examine cross-cultural differences in perceived quality of life and health-related behaviors on adolescents from southern Portugal and southern Spain. Sample consists in 319 adolescents. The Kidscreen-27 child self-report, a short version of Health Behavior in School-aged Children Questionnaire, and a Socio-demographic questionnaire were used. Results suggest significant differences between Portuguese and Spanish adolescents health behaviors. Portuguese adolescents experiment more legal drugs and consume more wine and beer. More Spanish adolescents smoke. No differences were found between countries on hashish use, liquor consumption, inebriation, and on the age of first sexual intercourse. Spanish adolescents perceived themselves with better quality of life. Gender differences were found on several dimensions of Quality of Life. Results are discussed with previous research on these topic and might be considered by nurses when promoting adolescent health.